Inhibition of C3 with pegcetacoplan results in normalization of hemolysis markers in paroxysmal nocturnal hemoglobinuria - Wong, Raymond S. M.; Pullon, Humphrey W. H.; Amine, Ismail; Bogdanovic, Andrija; Deschatelets, Pascal; Francois, Cedric G.; Ignatova, Kalina; Issaragrisil, Surapol; Niparuck, Pimjai; Numbenjapon, Tontanai; Roman, Eloy; Sathar, Jameela; et al. (Annals of hematology, 2022)
Paroxysmal nocturnal hemoglobinuria (PNH) is a rare, acquired hematologic disorder characterized by complement-mediated hemolysis. C5 inhibitors (eculizumab/ravulizumab) control intravascular hemolysis but do not prevent residual extravascular hemolysis. The newly approved complement inhibitor, pegcetacoplan, inhibits C3, upstream of C5, and has the potential to improve control of complement-mediated hemolysis. The PADDOCK and PALOMINO clinical trials assessed the safety and efficacy of pegcetacoplan in complement inhibitor-naïve adults (≥ 18 years) diagnosed with PNH. Patients in PADDOCK (phase 1b open-label, pilot trial) received daily subcutaneous pegcetacoplan (cohort 1: 180 mg up to day 28 [ n = 3]; cohort 2: 270–360 mg up to day 365 [ n = 20]). PALOMINO (phase 2a, open-label trial) used the same dosing protocol as PADDOCK cohort 2 ( n = 4). Primary endpoints in both trials were mean change from baseline in hemoglobin, lactate dehydrogenase, haptoglobin, and the number and severity of treatment-emergent adverse events. Mean baseline hemoglobin levels were below the lower limit of normal in both trials (PADDOCK: 8.38 g/dL; PALOMINO: 7.73 g/dL; normal range: 11.90–18.00 g/dL), increased to within normal range by day 85, and were sustained through day 365 (PADDOCK: 12.14 g/dL; PALOMINO: 13.00 g/dL). In PADDOCK, 3 serious adverse events (SAE) led to study drug discontinuation, 1 of which was deemed likely related to pegcetacoplan and 1 SAE, not deemed related to study drug, led to death. No SAE led to discontinuation/death in PALOMINO. Pegcetacoplan was generally well tolerated and improved hematological parameters by controlling hemolysis, while also improving other clinical PNH indicators in both trials. These trials were registered at www.clinicaltrials.gov (NCT02588833 and NCT03593200).